Designing Problem Based Learning (Pbl) Problem Scenario For Statistic Using Linear And Non - Linear Multimedia Presentation - W. Mohd Puzi, W. Nurnadiah; Shahbodin, Faaizah; Hussin, Burairah (2009)
Problem Based Learning (PBL) is an instructional method that is known to offer students with knowledge suitable for problem solving. In order to test this assertion the process of problem based learning is described and measured against three principle of learning: activation of prior knowledge, elaboration and encoding specificity. Using PBL method, students' understanding with regards to the problem scenario is very significant process. One of the main defining characteristic of PEL, which distinguishes it from some other method, is that the problem is presented to the students first at the start learning process. Traditionally, problem scenario is presented in a printed text, which is not tempting for student to understand the motive behind it. Information and Communication Technology (ICT) on the other hand has widely accepted in many areas which include education as well. By applying multimedia presentation as a discipline in ICT, it is believed that it could helps in designing the effective problem scenario. The purpose of this study is to design and test the effectiveness of PEL problem scenario for subject Statistic using linear and non-linear multimedia presentation. Linear presentation is known as no navigation control is involved through that process while nonlinear presentation uses user interactivity to control the presentation. This paper discusses the early storyboard design and the icons that used.